Cellulose Nanocomposite Hydrogels: From Formulation to Material Properties - Butylina, Svetlana; Geng, Shiyu; Laatikainen, Katri; Oksman, Kristiina (Frontiers in Chemistry, 2020)
Poly(vinyl alcohol), PVA hydrogels produced using freeze-thaw method have attracted attention for a long time since their first preparation in 1975. Due to the importance of polymer intrinsic features and advantages, associated with them, they are very suitable for biomedical applications. This study focused on composite hydrogels which were produced by using different concentrations of PVA (5 and 10%) and cellulose nanocrystals (1 and 10 wt.%), also, pure PVA hydrogels were used as references. The main goal was to determine the impact of both components on mechanical, thermal and water absorption properties of composite hydrogels as well as on morphology and initial water content. It was found that the effect of PVA was dominating for all hydrogels. The effect of the CNC addition was both concentration-dependent and case-dependent. As a general trend, addition of CNC decreased the water content of the prepared hydrogels, decreased the crystallinity of the PVA and increased the hydrogels compression modulus and strength to some extent. The performance of composite hydrogels in cyclic compression test was studied; the hydrogel with low PVA (5) and high CNC (10) content showed totally reversible behavior after 10 cycles